The Role of Stakeholders in Strengthening Waste Bank Management in Pekanbaru City - Iskandar, Mario; Zuhdi, Sulaiman (Dinasti Publisher, 2026)
Urban waste management remains a critical challenge to sustainable development due to rising waste generation and the suboptimal implementation of the reduce reuse recycle approach. Waste banks have emerged as a community based alternative that emphasizes public participation and cross stakeholder collaboration. This study analyzes stakeholder roles in strengthening the management of the Mutiara The Gade Clean and Gold Waste Bank in Tuah Karya Village, Pekanbaru City, and identifies factors influencing its sustainability. A descriptive qualitative approach was employed using in depth interviews, observation, and documentation. Informants were selected through purposive and snowball sampling. Data were analyzed with the interactive model of Miles and Huberman. The findings show that stakeholder roles are not balanced. The private sector, particularly PT Pegadaian Persero, plays a dominant role through mentoring and operational support that improves management effectiveness and encourages participation. Conversely, the local government role as regulator and supervisor remains limited, especially in guidance, coordination, and sustained facilitation. Community participation is relatively strong in waste sorting and deposit activities, although challenges persist in incentive mechanisms. Weak cross stakeholder coordination and the absence of a sustainable collaborative governance model hinder management strengthening. This study concludes that stronger stakeholder synergy, long term commitment, and collaborative governance are essential to sustain community based waste bank management.